School bullying and non-suicidal self-injury among rural adolescents: the mediating role of alexithymia and the moderating role of friendship quality - Wen, Jing; Xu, Qinghong; Zhang, Hongjun; Ding, Jianli; Li, Min (Frontiers in Psychology, 2025)
This study investigates the relationship between school bullying and non-suicidal self-injury (NSSI) in adolescents, with a particular focus on the mediating role of alexithymia and the moderating effect of friendship quality. The present study employed the Bullying Questionnaire, the Toronto Alexithymia Scale, the Friendship Quality Questionnaire, and the Adolescent Non-Suicidal Self-Injury Assessment Questionnaire with 701 middle school students. The results indicate that (1) Student bullying significantly predicts NSSI (79.92%) and (2) alexithymia partially mediated this relationship (20.08%). Moreover, (3) friendship quality was identified as a significant moderator in the relationship between student bullying and NSSI (β = −0.07, p < 0.05). Furthermore, friendship quality also moderated the relationship between alexithymia and NSSI (β = −0.003, p < 0.01). In conclusion, the study highlights the mediating role of alexithymia and the moderating role of friendship quality, providing valuable insights for psychological interventions targeting adolescent populations and adding to the social buffer theory. Friendship quality may reduce non-suicidal self-injury and alleviate the symptoms of alexithymia, which explores friendship quality as a protective factor for alexithymia.